Assessing the efficacy of metacognitive therapy as monotherapy or adjunctive treatment in patient suffering from major depression and dysthimia: A comprehensive review of clinical trials - Zanini, C.; Enrico, P.; Pescuma, V.; Favalli, V.; Bressi, C.; Brambilla, P.; Delvecchio, G. (Journal of affective disorders, 2025)
Depression is one of the most widespread diseases worldwide, with the highest rates of disability. Considering its chronic course, over the years several treatment options have been developed and validated, however still with high relapse rates. Therefore, in recent years, the so-called third wave psychotherapies have been developed for the treatment of psychiatric disorders. Among these, the Metacognitive therapy (MCT) has proven to be effective in treating depression. The aim of this review is to evaluate the efficacy of MCT as monotherapy or adjunctive treatment in reducing depressive symptoms in patients suffering from major depression or dysthymia. From bibliographic research in PubMed until December 2023, we retrieved 12 original studies meeting our research criteria. The total sample of patients undergoing metacognitive therapy (MCT) included 376 individuals, while the control groups comprised 300 subjects, with a gender ratio of the participants of 0.48 %. The results show that metacognitive therapy is an effective approach in reducing depressive symptoms in patients with a diagnosis of depression or dysthymia when used as add-on therapy, with an efficacy comparable to CBT and superior to pharmacotherapy and as monotherapy, with an efficacy comparable to therapy with antidepressants compared to the control group and compared to cognitive-behavioral therapy with higher rates of reduction of depressive symptoms after treatment and at six months. Preliminary data also indicate its efficacy in terms of reduction of depressive symptoms in elderly people, suggesting its possible use in this population. The methodological heterogeneity in terms of treatment protocols of MCT and treatment control as well as the clinical heterogeneity of the sample employed may have limited the generalizability of the results. The results suggest that the use of MCT, both as monotherapy and as an add-on treatment, is a valid therapeutic option for major depression, even at the later stages. However, further studies are needed for deeper our comprehension of the efficacy of MCT in depression. •MCT, both as monotherapy and as an add-on treatment, reduces depressive and anxiety symptoms with high efficacy.•Studies demonstrate stable recovery rates up to 3 years post-treatment, suggesting lasting benefits of MCT.•MCT appears beneficial for non-responders to pharmacotherapy and those with poor drug tolerance, providing a viable alternative.•Future research should focus on refining MCT protocols, assessing its efficacy across diverse populations.